Brief Report: IFIH1 Mutation Causes Systemic Lupus Erythematosus With Selective IgA Deficiency. Issue 6 (June 2015) - Van Eyck, Lien; De Somer, Lien; Pombal, Diana; Bornschein, Simon; Frans, Glynis; Humblet‐Baron, Stéphanie; Moens, Leen; de Zegher, Francis; Bossuyt, Xavier; Wouters, Carine; Liston, Adrian
<x xml:space="preserve">Abstract</x> Objective To identify the underlying genetic defect in a 16‐year‐old girl with severe early‐onset and refractory systemic lupus erythematosus (SLE), IgA deficiency, and mild lower limb spasticity without neuroradiologic manifestations. Methods Whole‐exome sequencing and extensive immunologic analysis were performed on samples from the index patient. Results We identified a de novo p.R779H IFIH1 gain‐of‐function mutation in a patient with severe early‐onset SLE, selective IgA deficiency, and mild lower limb spasticity. The same mutation in IFIH1 was recently identified in patients with Aicardi‐Goutières syndrome, a rare neuroimmunologic disorder associated with elevated levels of type I interferon (IFN). IFN induced with helicase C domain 1 functions as an intracellular innate immune receptor that senses viral nucleic acids and leads to the induction of type I IFN and proinflammatory cytokines. Despite systemic immunosuppressive treatment, disease activity persisted in the patient and was associated with elevated serum levels of IFNα and up‐regulation of IFIH1 itself. Conclusion This finding adds a new genetic causation for Mendelian lupus and greatly extends the disease spectrum associated with mutations in IFIH1 (ranging from inflammatory encephalopathy to prototypic systemic autoimmune disease). This marked phenotypic heterogeneity, despite an identical mutation, demonstrates the importance of modifying factors in type I IFN–dependent pathologies caused by mutations in IFIH1.